Psychology, Health, Literature, and Management: An Integrative Systematic Review of Their Interdisciplinary Connections - Basu Dev Lamichhane; P Radha (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: Traditionally psychology, health, literature and management have grown as separate fields of knowledge, but now many modern societal and organizational issues require an interdisciplinary approach to be resolved. Psychological mechanisms affect health-related behaviors, wellbeing, learning, interpersonal relations, workplace productivity. Literature helps to understand emotions, identity, pain, empathy, conflicts and human relations, while management offers organizational context where wellbeing of individuals and teams can be facilitated. This review explores the connections between psychology, health, literature and management and highlights areas where collaboration between these disciplines is possible. Methods: This study used a systematic integrative literature review design. Peer-reviewed publications, systematic reviews, meta-analyses and bibliometric studies on the topic were found via searches in PubMed, publishers' databases, DOI-indexed scientific publications, NepJOL and other appropriate repositories. Prioritization was made in favor of recent publications from 2021 to 2026, but seminal theoretical and methodological works were kept where needed to provide explanations for certain established concepts. The inclusion criteria included research related to psychological wellbeing, health, literature or reading, workplace and organizational management, healthcare management and interaction of the mentioned areas. The evidence was analyzed thematically, not statistically. Results: The review suggests five major connections. First, psychological resources and psychological needs are closely linked to health and workplace wellbeing. Second, organizational demands and resources affect mental health, engagement, burnout and performance. Third, literature and reading can facilitate empathy, reflection, meaning creation and psychological wellbeing. Fourth, creative writing and arts interventions seem to be effective for mental health, although results are heterogeneous. Fifth, management strategies determine whether psychological and health resources are supported or deprived in organizations. Recently conducted Nepalese studies also demonstrate the importance of collaboration between psychological, health, educational, literary and management approaches. Conclusion: Psychology, health, literature, and management need to be seen as interrelated fields in solving complex issues related to humans and organizations. Such integration will promote humane healthcare, healthy workplace and learning environments, and responsible management. Novelty: This review offers an interdisciplinary conceptual framework linking psychological processes, health and wellbeing, literary experience, and management activities. This article also includes Nepalese scholarship within an international interdisciplinary dialogue.